Shakespeare and Feminism – Feminist Approaches to Shakespeare: Understanding Feminist Criticism in Shakespearean Literature (Journal of Advances and Scholarly Researches in Allied Education, 2014)
It is as difficult to define feminist criticism as it is to definefeminism, itself. Invariably, feminist criticism concentrates on women, payingattention to women’s position both in literature and culture. However, femalerepresentation is not the only focal point of feminist criticism, which alsoexamines relationships between men and women, social structures, and howsociety shapes individual identities and vice versa. More generally, it focuseson the extent the individual is able to influence social institutions andculture. It is important to emphasize that it is not enough to be a woman inorder to be labelled a feminist critic. Feminist critics should bedistinguished from female critics. Feminist criticism entails more thanconcentrating on female characters and analyzing certain specific subjectmatters; it is rather a matter of perspective. Even a man can be a feminist criticif he shares this particular perspective and bent of critical thinking.